Nationwide Survey of Middle Meningeal Artery Embolization for Chronic Subdural Hematoma in Japan - Satoshi MURAI; Yuki EBISUDANI; Jun HARUMA; Masafumi HIRAMATSU; Tomohito HISHIKAWA; Tetsu SATOW; Kenji SUGIU (Neurologia Medico-Chirurgica)
Middle meningeal artery embolization has increasingly been used to treat chronic subdural hematoma. However, the current state of its application and outcomes in Japan remains unclear. We conducted a multicenter observational study involving facilities affiliated with the Japanese Society for Neuroendovascular Therapy to assess current practices and clarify the usefulness and safety of middle meningeal artery embolization for chronic subdural hematoma. A total of 466 patients from 40 facilities were included. The mean age of the patients was 78.0 ± 10.5 years, and bleeding risks, including antithrombotic therapy or bleeding predisposition, were present in 36.1% of patients. The most common timing for middle meningeal artery embolization was after the second burr hole surgery, accounting for 34.8% of cases. N-butyl-2-cyanoacrylate was used as the embolic material in 67% of cases. The complication rate was 5.2%, with complication-related morbidity at 0.9%. Hematomas were stable in 91.5% of cases at 30 days post-middle meningeal artery embolization. The symptomatic recurrence rate was 8.9%. Cases that underwent middle meningeal artery embolization after the second or subsequent burr hole surgeries were significantly associated with symptomatic recurrence. This study is the first nationwide survey investigating the real-world clinical practice of middle meningeal artery embolization for chronic subdural hematoma in Japan. While it included many elderly patients, recurrent cases, and those with bleeding risks, the safety and usefulness of middle meningeal artery embolization were deemed acceptable. However, symptomatic recurrence was common even in cases with middle meningeal artery embolization when performed after the second or subsequent burr hole surgeries. A further prospective study will be warranted to clarify treatment indications, optimal timing, and treatment techniques of middle meningeal artery embolization.